Leading causes of fever in patients with liver function disorders - V. T. Ivashkin; M. A. Morozova; M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. Analysis of literature data on the possible causes of fever at patients with disorders of liver function. Article presents pathophysiological mechanisms of development of fever. The algorithm of assessment of patient with disorder of liver function and fever is submitted.Original positions. Fever in patients with liver failure can be caused both by infectious and non-infectious causes. Infections are the most frequent causes of fever at disorder of the liver function, that accounts for immunodeficiency state at this category of patients. An important role in development of fever at patients with liver cirrhosis is bacterial overgrowth syndrome, bacterial translocation processes and, as a consequence, endotoxemia. If the site of infection is not detected, it is necessary to keep in mind the option of development of non-infectious fever within acute phase reaction, neoplastic process or reaction to applied pharmaceutical agents.Conclusion. At development of fever at patients with liver failure carrying out differential diagnostics of the causes of body temperature elevation is necessary that allows more differentiated approaches to treatment.